Testing and Applications of Non-Linear Wave Shaping Circuits Based on Zener Diodes at Cryogenic Temperatures - El-Maksood, A. M. Abd (JOURNAL OF ADVANCES IN PHYSICS, 2017)
Applications of wave-shaping clipping circuits based on Zener diodes are of great interest in a wide range of modern electronic systems. As well, given the strong interest in space research and trips to distant planets, where the journey takes long periods. Therefore, the matter requires reliance on electronic systems with special specifications commensurate with the nature of the extremely low-temperature environments, down to cryogenic level (around 90 K). So, the present paper was concerned with studying the stability of the performance of different non-linear wave-shaping systems, based on silicon Zener diodes, whenever operates at very low temperatures down to cryogenic levels. From which, it is clear that for BZX79-C4V7 and BZX79-C5V6 Zeners, such electronic systems were shown to be insensitive to temperature variations. On the other hand, low breakdown voltage Zeners (BZV86-1V4 and BZX83-C3V6), the clipping edges were shown to be increased with lowering temperatures from 300 K down to 93 K. Finally, for Zener diodes with VZ greater than 6.0 V (BZX83-C6V8 and BZX55C9V1), the temperature coefficient is positive, so the clipping edges decrease with lowering temperatures, for the same range of temperatures.